Phase IIa randomized double‐blind, placebo‐controlled study of inhaled apomorphine as acute challenge for rescuing 'off' periods in patients with established Parkinson's disease. Issue Volume 20:Issue11(2013:Nov.) (28th January 2013) - Grosset, K. A.; Malek, N.; Morgan, F.; Grosset, D. G.
<x xml:space="preserve">Abstract</x> Background and purpose In this first study of inhaled apomorphine (VR040) in patients with Parkinson's disease, the primary objective was to find the minimum efficacious dose of apomorphine that was useful in rescuing patients during 'off' periods. Safety, tolerability and pharmacokinetics of inhaled apomorphine were assessed during the study. Methods A double‐blind, placebo‐controlled, randomized trial of three escalating single doses of inhaled apomorphine (0.2, 0.5 and 0.8 mg fine particle dose) versus placebo (3 : 1 active:placebo) was performed. Parkinson's motor severity assessments by a clinician, and disease state assessment by the patient, were performed at baseline during an 'off' state, and at specified times after test drug administration. Safety assessments (including vital signs, electrocardiogram and forced expiratory volume) were performed, and plasma apomorphine levels measured. Results All 24 patients completed the study, and considering the three dose levels together, inhaled apomorphine did not significantly increase the proportion of patients switching from 'off' to 'on' (0/6 at 0.2 mg, 3/6 at 0.5 mg and 2/6 at 0.8 mg vs. 1/6 for placebo), or decrease the time from 'off' to 'on' post‐treatment (10 min for 0.5 mg, 40 min for 0.8 mg, vs. 20 min for placebo). However, there was a suggestion of benefit at the higher doses (5/12 switched 'on' at the 0.5 or 0.8 mg doses, vs. 1/6 for placebo). There were no serious adverse events and treatment was well tolerated. Peak plasma concentration was 1–3 min post‐dose, and plasma level dose proportionality was observed. Conclusions Inhaled apomorphine was safe and well tolerated at the doses tested for an acute challenge to rescue 'off' periods, but efficacy at these doses was limited. A follow‐up study at higher doses is appropriate given these initial findings.